Subkutanes pannikulitisartiges T-Zell-Lymphom: zwei Kasuistiken = Subcutaneous panniculitis-like T-cell lymphoma : two case reports - Wagner, Gunnar; Klemke, Claus-Detlev (Der Hautarzt, 2016)
Histopathology, immunohistochemical, and molecular genetic findings revealed the diagnosis of subcutaneous panniculitis-like T-cell-lymphoma in two patients, aged 44 and 70 years. The clinical morphology of the lymphoma manifestations showed varied significantly. One patient presented with a singular erythematous nodule in the chin region. The other patient suffered from extended plate-like resistances and atrophy of the face, upper arms and left breast. Hemophagocytic syndrome was not present in either patient. Prognosis of subcutaneous panniculitis-like T-cell lymphoma without associated hemophagocytic syndrome is reported to be favorable. Radiotherapy of the singular lesion on the chin and systemic corticosteroids of the extended plaques induced complete remission in both patients.
Gesehen am 20.05.2019
Online publiziert: 16. Dezember 2015